The Pragmatics of Dystopia: Linguistic Impoliteness as a Tool for Power and Resistance in “Alephia 2053” Movie - Hafidh, Ahmad Nur; Al Anshory, Abdul Muntaqim (Jurnal Bahasa dan Sastra, 2025)
This study fills a gap in pragmatic research by applying the theories of Bousfield, Terkourafi, and Locher to analyze linguistic impoliteness as represented in the animated movie Alephia 2053 by Rabi’ Sweidan. This approach contributes new insights to Arabic fictional media by demonstrating that impoliteness reflects power relations within a dystopian narrative. The study aims to identify various forms of linguistic impoliteness in the dialogues of Alephia 2053. A descriptive qualitative method is employed to analyze the movie’s dialogues, focusing on the integrated framework of Bousfield, Terkourafi, and Locher, which combines speaker intention, social norms, and interpersonal relations to explain the complexity of impoliteness in political cinematic discourse. The primary data consist of dialogues from Rabi’ Sweidan’s Alephia 2053, while the secondary data include books and journal articles relevant to the research topic. Data collection techniques involve observation, note-taking, and documentation. The analytical process includes three main stages: data reduction, data presentation, and conclusion drawing. The findings reveal five categories of impoliteness: carelessness (2 utterances), face play (9 utterances), face degradation (30 utterances), face threat (19 utterances), and face attack (11 utterances). The results indicate that face degradation is the most dominant form, with 30 utterances, highlighting that Alephia 2053 not only presents linguistic impoliteness but also represents power relations, social criticism, and resistance to authoritarian regimes within mediated political discourse.